Awn Morphology Influences Dispersal, Microsite Selection and Burial of Australian Native Grass Diaspores - Cavanagh, Annette M.; Morgan, John W.; Godfree, Robert C. (Frontiers in Ecology and Evolution, 2020)
Seed dispersal is a vital part of a plant’s life cycle that enables progeny to reach new sites suitable for burial and establishment. Awns are characteristic of many grass species and enable diaspores to self-disperse. Little is known, however, about the role of different awn morphologies in dispersal or burial. The objective of this study was to investigate the influence of awn morphology on diaspore surface dispersal and burial among representative Australian Poaceae. Surface dispersal, burial and microsite selectivity of diaspores were compared across 30 grass species and ten awn morphological types using laboratory and natural simulation experiments. The presence of an awn significantly facilitated surface dispersal and burial of diaspores, with awn length and hygroscopic activity being positively related to both surface dispersal and burial depth. Geniculate (once-bent) and bigeniculate (twice-bent) awns were the most efficient at surface dispersal. Burial efficiency, however, was influenced by microsite conditions; a surface obstruction increased burial for almost all awn types, while falcate (curved)-awned species were effective at burying without such objects. This study indicates that awn morphologies likely play different functional roles in the success of Australian grass progeny.